Ethanol Alters Variability, but not Rate, of Firing in Medial Prefrontal Cortex Neurons of Awake, Behaving Rats. - Morningstar, Mitchell D. (Alcohol Clin Exp Res, 2020)
BACKGROUND: The medial prefrontal cortex (mPFC) is a brain region involved in the evaluation and selection of motivationally relevant outcomes. Neural activity in mPFC is altered following acute ethanol (EtOH) use and, in rodent models, doses as low as 0.75 g/kg yield cognitive deficits. Deficits in decision-making following acute EtOH are thought to be mediated, at least in part, by decreases in mPFC firing rates (FRs). However, the data leading to this conclusion have been generated exclusively in anesthetized rodents. The present study characterizes the effects of acute EtOH injections on mPFC neural activity in awake-behaving rodents. METHODS: Awake-behaving and anesthetized in vivo electrophysiological recordings were performed. We utilized three groups: the first received two saline injections, the second received a saline injection followed by 1.0 g/kg EtOH, the last received saline followed by 2 g/kg EtOH. One week later an anesthetized recording occurred where a saline injection was followed by an injection of 1.0 g/kg EtOH. RESULTS: The anesthetized condition showed robust decreases in neural activity and differences in up-down state dynamics. In the awake-behaving condition, FRs were grouped according to behavioral state: moving, not moving, and sleep. The differences in median FRs were found for each treatment and behavioral state combination. A FR decrease was only found in the 2.0 g/kg EtOH treatment during not moving states. However, robust decreases in FR variability were found across behavioral state in both the 1.0 g/kg and 2.0 g/kg EtOH treatment. Sleep was separately analyzed. EtOH modulated the up-down states during sleep producing decreases in FRs. CONCLUSIONS: In conclusion, the changes in neural activity following EtOH administration in anesthetized animals are not conserved in awake-behaving animals. The most prominent difference following EtOH was a decrease in FR variability suggesting that acute EtOH may be affecting decision-making via this mechanism.